SC75741 antagonizes vesicular stomatitis virus, duck Tembusu virus, and duck plague virus infection in duck cells through promoting innate immune responses - Tian, Bin (Poult Sci, 2021)
Duck Tembusu virus (DTMUV) and duck plague virus (DPV) are typical DNA and RNA viruses of waterfowl, causing drastic economic losses to the duck farm industry in terms of high mortality and decreased egg production. These 2 viruses reappear from time to time because the available vaccines fail to provide complete immunity and no clinical antiviral drugs are available for them. In the present study, we evaluated the antiviral activity of SC75741 for DTMUV, DPV, and the model virus, vesicular stomatitis virus infection in duck cells. SC75741, a nuclear factor-kappa B (NF-κB)-specific inhibitor in mammal cells, revealed the highest antiviral activity among the inhibitors specific to c-Jun NH(2)-terminal kinase, extracellular signal-regulated kinase, p38 mitogen-activated protein kinase (p38), and NF-κB signaling. The antiviral activity of SC75741 was dose-dependent and showed effects in different duck cell types. Time-addition and duration assay demonstrated that SC75741 inhibited virus infection in the middle of and after virus infection at least for 72 h in duck embro fibroblast cells. The DPV viral adsorption and genomic copy number were reduced, indicating that SC75741 blocks the phase of the virus life cycle at viral entry and genomic replication. In addition, SC75741 enhanced the expression of interferon only when stimulator of interferon genes (STING) was overexpressed or pre-activated by the virus infection, suggesting that SC75741 acts as a STING agonist. In conclusion, SC75741 is a candidate antiviral agent for DTMUV and DPV.